Biomechanical comparison of locking plate and pin-tension band wiring fixation for 3D-printed canine patellar fracture repair - Jung, Seung-Gi; Kim, Hwi-Yool (Frontiers in Veterinary Science, 2025)
IntroductionThe conventional pin and tension band wiring (TBW) technique remains the standard for fixation, but is frequently associated with complications such as wire breakage, loosening, and delayed healing in patellar fracture. Locking plate fixation has demonstrated superior biomechanical stability in human studies. This study aimed to compare the biomechanical performance of locking plate fixation versus TBW in canine transverse patellar fractures and to evaluate the influence of plate design on fixation strength.MethodsThirty 3D-printed canine patellar fracture models were fabricated based on CT data from a 45 kg Akita dog and allocated into three groups (n = 10 per group): Group 1—pin/TBW fixation, Group 2—2-hole locking plate fixation, Group 3—4-hole locking plate fixation. All models were subjected to tensile testing at a 135° stifle angle to simulate quadriceps force. Fixation failure was defined as a fracture gap displacement greater than 2 mm or structural yielding.ResultsGroup 1 showed progressive displacement with increasing tensile load (1 mm: 226.4 ± 26.2 N; 2 mm: 280.8 ± 27.7 N; 3 mm: 342.7 ± 27.0 N). Groups 2 and 3 exhibited less than 1 mm displacement and significantly higher maximum failure loads (Group 2: 505.6 ± 66.6 N; Group 3: 556.9 ± 39.6 N; p < 0.05). No significant difference was observed between the 2-hole and 4-hole plate groups.DiscussionLocking plate fixation demonstrated significantly superior biomechanical stability compared to the traditional pin/TBW technique in a canine transverse patellar fracture model. The comparable performance of the smaller 2-hole locking plate suggests its potential utility in clinical applications, particularly for small-breed dogs. These findings support the clinical applicability of locking plate systems as a reliable alternative for patellar fracture stabilization in veterinary practice.